Exploring the feasibility, effectiveness, and acceptability of telehealth for delivering a pain management group program: A retrospective study - Ramony Chan; Bernadette Brady; Judy Zou; Matthew McMullan; Sandhiya Ali; Subram Naidu; Renata Bazina (PLoS ONE, 2025)
Objective The COVID-19 pandemic caused significant changes in healthcare, particularly in pain management. To maintain care, the Multidisciplinary Activity Improvement Program (MAiP), at the Department of Pain Medicine, Liverpool Hospital, was adapted for delivery through telehealth. Although MAiP’s effectiveness is well-documented, its telehealth adaptation has not been studied. This study retrospectively assesses the feasibility, effectiveness trends, and acceptability of a telehealth-based pain program. Methods Using a single-group retrospective cohort design, participants were patients who completed the telehealth-based MAiP between 2020 and 2022. Primary outcomes: pain severity, pain interference, anxiety, stress, depression, pain self-efficacy, and pain catastrophising, were evaluated pre- and post-treatment. Participants’ satisfaction with the program was assessed through a post-program survey. Data analysis employed a generalised estimation equation modelling technique. Results 33 patients were enrolled in a telehealth MAIP during the study period, with outcomes available for 22 patients (68% female, mean age 51.45 ± 10.41, 72.7% with pain duration >5 years). Significant improvements were observed in the primary outcome measures, indicating the effectiveness of the telehealth-based MAiP. Standardised effect sizes (ES) for all outcomes ranged from small to large. Of the 22 participants, 14 completed the satisfaction survey, with the majority expressing satisfaction and finding the telehealth-based program beneficial. Conclusion The study’s findings present initial evidence for the effectiveness and acceptability of delivering pain management group programs via telehealth, expanding the range of services available to patients. These promising results advocate for continued exploration of telehealth as a vital avenue for pain management service delivery, warranting further investigation and advancement in this evolving field.